INTERDEPENDENSI KEBIJAKAN DEVIDEN, FINANCIAL LEVERAGE DAN INVESTASI: PENGUJIAN PECKING ORDER THEORY - Nency Liono; Mudji Utami; Liliana Inggrit Wijaya (Journal of Management and Business, 2009)
The aims of this research to find interdependency relationships among dividend policy, financial leverage, and investment based on pecking order theory testing. Research object includes food and beverages industry which listing in Indonesian Stock Exchange 2002-2007. Given the influence among third the variable hence will know what is there are interdependency among third the variable and what its influence to company in period food and beverage industry 2002-2007 related to company financial decision. Result of this research shows there is interdependency among dividend policy, financial leverage and investment but not support pecking order theory.